Anti-rust heat shrinkage film and preparation method thereof

By using an anti-rust heat shrink film composed of a support layer, an adhesive layer and a modified polyethylene layer, the problem of degradation of mechanical properties and anti-rust properties of the existing heat shrink film after long-term use is solved, and efficient anti-rust and mechanical strength improvement are achieved.

CN119682352APending Publication Date: 2025-03-25HANGZHOU JINHANG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411904561.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

After long-term use of the existing heat shrink film, its mechanical properties and anti-rust performance have decreased, and it is impossible to maintain a good anti-rust effect.

Method used

An anti-rust heat shrink film consisting of two support layers, two adhesion layers and one isolation layer is adopted. The support layer is a linear low-density polyethylene and low-density polyethylene blend layer, the adhesion layer is an ethylene-vinyl acetate resin layer, and the isolation layer is a modified polyethylene layer, which contains a gas-phase anti-rust masterbatch and an anti-rust aerogel.

Benefits of technology

The mechanical properties and rust-proof properties of the heat shrink film are improved, the long-term anti-rust effect is achieved, and the film's ability to isolate oxygen and water vapor is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204078470000071
    Figure BDA0005204078470000071
  • Figure BDA0005204078470000081
    Figure BDA0005204078470000081
Patent Text Reader

Abstract

The invention relates to the field of heat shrinkage films, and particularly discloses an anti-rust heat shrinkage film and a preparation method thereof. The antirust heat shrink film comprises two supporting layers, two adhesion layers and an isolation layer, the isolation layer is located between the two supporting layers, the adhesion layers are located between the isolation layer and the supporting layers, the supporting layers are linear low-density polyethylene and low-density polyethylene blending layers, the adhesion layers are ethylene-vinyl acetate resin layers, and the isolation layer is an ethylene-vinyl acetate resin layer. The isolating layer is a modified polyethylene layer, and the modified polyethylene layer is prepared from the following raw materials in parts by mass: 50 to 75 parts of polyethylene, 2.5 to 3.7 parts of gas-phase anti-rust master batch and 5 to 8 parts of anti-rust aerogel; in addition, the preparation method has the advantage of improving the anti-rust performance of the heat shrinkage film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of heat shrinkable films, and more specifically, to an anti-rust heat shrinkable film and a preparation method thereof. Background Art

[0002] Heat shrink film is widely used in real life in the packaging process. The heat shrink film material will go through a shrinking molding stage and fit tightly to the surface of the packaged item. As the outer packaging of the product, it can form a protective layer similar to plastic sealing, effectively isolating moisture and preventing the package from being opened without authorization, thereby ensuring the dryness and integrity of the original packaged product.

[0003] However, with the development of science and technology, new requirements have been put forward for the anti-rust function of heat shrinkable film. The heat shrinkable film itself should have good mechanical properties and be not easy to be damaged during the long-term anti-rust process. At the same time, the heat shrinkable film can better isolate oxygen and water vapor. However, the existing heat shrinkable film has a decrease in mechanical properties and anti-rust performance after long-term use. After long-term use, it is impossible to maintain good anti-rust performance. Summary of the invention

[0004] In order to improve the anti-rust performance of a heat shrinkable film, the present application provides an anti-rust heat shrinkable film and a preparation method thereof.

[0005] In a first aspect, the present application provides an anti-rust heat shrinkable film, which adopts the following technical solution: A rust-proof heat shrinkable film comprises two supporting layers, two adhesive layers and an isolation layer, wherein the isolation layer is located between the two supporting layers, the adhesive layer is located between the isolation layer and the supporting layer, the supporting layer is a blended layer of linear low-density polyethylene and low-density polyethylene, the adhesive layer is an ethylene-vinyl acetate resin layer, the isolation layer is a modified polyethylene layer, and the modified polyethylene layer comprises the following raw materials in parts by mass: 50-75 parts of polyethylene, 2.5-3.7 parts of vapor phase rust-proof masterbatch, and 5-8 parts of rust-proof aerogel.

[0006] By adopting the above technical scheme, the support layer is a blended layer of linear low-density polyethylene and low-density polyethylene, which has good mechanical properties and strength, and can provide good support for the anti-rust heat shrink film. The adhesion layer is an ethylene-vinyl acetate resin layer, which has good adhesion strength and can compound the support layer with the isolation layer. The modified polyethylene layer contains gas phase anti-rust masterbatch, which can slowly volatilize the anti-rust particles outward to form an anti-rust layer on the surface of the object in the heat shrink film, reducing its corrosion. At the same time, the volatilization rate of the gas phase anti-rust masterbatch is low, which can achieve a long-term anti-rust function. The addition of anti-rust aerogel can enhance the mechanical properties of the isolation layer, thereby enhancing the mechanical properties of the anti-rust heat shrink film. At the same time, the anti-rust aerogel contains corrosion inhibitors, which can further improve the anti-rust performance of the anti-rust heat shrink film.

[0007] Preferably, the anti-rust aerogel is a silica aerogel added with a composite gas phase corrosion inhibitor, and the added amount of the composite gas phase corrosion inhibitor is 1.22-2.35wt% of the total weight of the anti-rust aerogel.

[0008] By adopting the above technical scheme, a composite gas phase corrosion inhibitor is added to the silica aerogel, so that the silica aerogel can slowly release the gas phase corrosion inhibitor to the outside, and cooperate with the gas phase anti-rust masterbatch to extend the anti-rust period while making the anti-rust effect within the anti-rust period better. At the same time, the addition of anti-rust aerogel can improve the mechanical properties of the anti-rust heat shrink film.

[0009] Preferably, the composite vapor phase corrosion inhibitor comprises sodium nitrite, sodium benzoate and dicyclohexylamine octanoate in a mass ratio of (0.76-0.83):(1.16-1.32):(0.54-0.63).

[0010] By adopting the above technical scheme, sodium nitrite, sodium benzoate and dicyclohexylamine octanoate all have good volatility and anti-rust performance. The three are compounded according to the mass ratio to have a synergistic effect and can further improve the anti-rust performance.

[0011] Preferably, the method for preparing the rust-proof aerogel comprises the following steps: dissolving hydrochloric acid and hexadecyltrimethylammonium bromide in water, mixing them evenly, adding methyltriethoxysilane, stirring at 20-25°C for 2-2.5h, adding a composite vapor phase corrosion inhibitor, stirring until the mixture is evenly mixed, adding ammonia water, standing at 75-80°C to obtain a wet gel, washing, and drying to obtain the rust-proof aerogel.

[0012] By adopting the above technical scheme, methyltriethoxysilane is hydrolyzed to form gel under alkaline conditions, and before adding ammonia water for gelation, a composite gas phase corrosion inhibitor is added so that the composite gas phase corrosion inhibitor is evenly dispersed in the wet gel to obtain an anti-rust aerogel.

[0013] Preferably, the wet gel is further treated as follows after washing and before drying: 18-23 wt % tert-butyl alcohol solution of methyltrimethoxysilane is added to the washed wet gel, reacted for 11-12 hours, and then freeze-dried.

[0014] By adopting the above technical scheme, after the wet gel is treated, methyltrimethoxysilane enters the wet gel by diffusion, and the silica gel particles are hydrophobically modified, so that the surface of the wet gel is connected with hydrophobic methyl groups. The shrinkage of the wet gel is reduced during the drying process, and a loose and porous structure is presented, which enhances the hydrophobicity of the rust-proof aerogel, improves the porosity and structural strength of the rust-proof aerogel, and thereby improves the bonding between the rust-proof aerogel and polyethylene and the mechanical strength of the isolation layer.

[0015] Preferably, the modified polyethylene layer further comprises modified lignin, and the added amount of the modified lignin is 2.65-3.49 wt % of the polyethylene.

[0016] By adopting the above technical scheme, the modified lignin has good antioxidant properties. Adding modified lignin to the modified polyethylene layer can effectively improve the oxygen and water barrier properties of the modified polyethylene layer, and can effectively reduce the entry of oxygen and water vapor into the anti-rust shrink film, thereby improving the anti-rust performance of the anti-rust shrink film.

[0017] Preferably, the preparation method of the modified lignin comprises the following steps: dissolving alkali lignin in N'N-dimethylformamide, adding imidazole and tert-butyldimethylchlorosilane, and stirring at 20-25°C for 12-13h, removing N'N-dimethylformamide in vacuo, adding water for precipitation, filtering, centrifugal washing, and drying to obtain modified lignin.

[0018] By adopting the above technical scheme, methyl silylation treatment is performed on alkali lignin using tert-butyldimethylchlorosilane, thereby improving the dispersibility of lignin in the modified polyethylene layer, enabling it to be compounded with the modified polyethylene, and improving the mechanical properties of the isolation layer and the barrier properties to oxygen and water vapor.

[0019] In a second aspect, the present application provides a method for preparing an anti-rust heat shrinkable film, which adopts the following technical solution: A method for preparing an anti-rust heat shrink film comprises the following steps: mixing polyethylene, gas phase anti-rust masterbatch and anti-rust aerogel, melt-extruding and preparing an isolation layer raw material for standby use, feeding a support layer raw material, an adhesion layer raw material and an isolation layer raw material separately, performing five-layer co-extrusion, and blow-molding to form a film to prepare the anti-rust heat shrink film.

[0020] By adopting the above technical solution, the prepared rust-proof heat shrinkable film has good rust-proof performance, can isolate oxygen and water vapor to protect the objects in the rust-proof heat shrinkable film, and has a long-term rust-proof function.

[0021] In summary, this application has the following beneficial effects: 1. In the present application, the support layer is a blended layer of linear low-density polyethylene and low-density polyethylene, which has good mechanical properties and strength, and can provide good support for the anti-rust heat shrinkable film. The adhesion layer is an ethylene-vinyl acetate resin layer, which has good adhesion strength and can compound the support layer with the isolation layer. The modified polyethylene layer contains a vapor phase anti-rust masterbatch, which can slowly volatilize the anti-rust particles outward, so that it forms an anti-rust layer on the surface of the object in the heat shrinkable film, reducing its corrosion. At the same time, the volatilization rate of the vapor phase anti-rust masterbatch is low, and a long-term anti-rust function can be achieved. The addition of anti-rust aerogel can enhance the mechanical properties of the isolation layer, thereby enhancing the mechanical properties of the anti-rust heat shrinkable film. At the same time, the anti-rust aerogel contains a corrosion inhibitor, which can further improve the anti-rust performance of the anti-rust heat shrinkable film.

[0022] 2. In the present application, a composite gas phase corrosion inhibitor is added to the silica aerogel, so that the silica aerogel can slowly release the gas phase corrosion inhibitor to the outside, and cooperate with the gas phase anti-rust masterbatch to extend the anti-rust period while making the anti-rust effect within the anti-rust period better. At the same time, the addition of anti-rust aerogel can improve the mechanical properties of the anti-rust heat shrink film.

[0023] 3. In the present application, after the wet gel is treated, methyltrimethoxysilane enters the wet gel by diffusion, and the silica gel particles are hydrophobically modified, so that the surface of the wet gel is connected with hydrophobic methyl groups. The shrinkage of the wet gel is reduced during the drying process, and a loose and porous structure is presented, which enhances the hydrophobicity of the anti-rust aerogel, improves the porosity and structural strength of the anti-rust aerogel, and thereby improves the bonding between the anti-rust aerogel and polyethylene and the mechanical strength of the isolation layer. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] Preparation Example 1-10 of Anti-Rust Aerogel Preparation Example 1 The rust-proof aerogel is a silica aerogel added with a composite gas phase corrosion inhibitor. The preparation method of the rust-proof aerogel comprises the following steps: dissolving 0.08 mL of hydrochloric acid and 0.82 g of hexadecyltrimethylammonium bromide in water, mixing evenly, adding 4.8 mL of methyltriethoxysilane, stirring at 20°C for 2.5 hours, adding the composite gas phase corrosion inhibitor, stirring until the mixture is evenly mixed, adding 2.8 mL of 15 wt% ammonia water, standing at 75°C to obtain a wet gel, washing and drying to obtain the rust-proof aerogel, wherein the addition amount of the composite gas phase corrosion inhibitor is 2.35 wt% of the total weight of the rust-proof aerogel, and the composite gas phase corrosion inhibitor comprises sodium nitrite, sodium benzoate and dicyclohexylamine octanoate in a mass ratio of 0.76:1.16:0.54.

[0026] Preparation Example 2 The rust-proof aerogel is a silica aerogel added with a composite gas phase corrosion inhibitor. The preparation method of the rust-proof aerogel comprises the following steps: dissolving 0.07 mL of hydrochloric acid and 0.75 g of hexadecyltrimethylammonium bromide in water, mixing evenly, adding 3.7 mL of methyltriethoxysilane, stirring at 25° C. for 2 hours, adding the composite gas phase corrosion inhibitor, stirring until the mixture is evenly mixed, adding 2.2 mL of 15 wt% ammonia water, standing at 80° C. to obtain a wet gel, washing and drying to obtain the rust-proof aerogel, wherein the addition amount of the composite gas phase corrosion inhibitor is 1.22 wt% of the total weight of the rust-proof aerogel, and the composite gas phase corrosion inhibitor comprises sodium nitrite, sodium benzoate and dicyclohexylamine octanoate in a mass ratio of 0.83:1.32:0.63.

[0027] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the added amount of the composite vapor phase corrosion inhibitor is 0.52 wt % of the total weight of the anti-rust aerogel.

[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the added amount of the composite vapor phase corrosion inhibitor is 3.65 wt % of the total weight of the anti-rust aerogel.

[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the composite vapor phase corrosion inhibitor includes sodium nitrite, sodium benzoate, and dicyclohexylamine octanoate in a mass ratio of 0.76:0.25:1.21.

[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the composite vapor phase corrosion inhibitor includes sodium nitrite, sodium benzoate, and dicyclohexylamine octanoate in a mass ratio of 0.76:1.89:0.23.

[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 1 is that in Preparation Example 7, the wet gel is subjected to the following treatment after washing and before drying: 2.1 mL of 23 wt % methyltrimethoxysilane tert-butanol solution is added to the washed wet gel, reacted for 11 h, and then freeze-dried.

[0032] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 1 is that in Preparation Example 8, the wet gel is subjected to the following treatment after washing and before drying: 2.7 mL of 18 wt % methyltrimethoxysilane tert-butanol solution is added to the washed wet gel, reacted for 12 h, and then freeze-dried.

[0033] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 7 is that in Preparation Example 9, the concentration of the tert-butyl alcohol solution of methyltrimethoxysilane is 12 wt %.

[0034] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that in Preparation Example 10, the concentration of the tert-butyl alcohol solution of methyltrimethoxysilane is 32 wt %.

[0035] Preparation Example 11-12 of Modified Lignin Preparation Example 11 The preparation method of modified lignin comprises the following steps: dissolving 0.9 g of alkali lignin in 4.8 mL of N'N-dimethylformamide, adding 0.23 mg of imidazole and 0.35 mg of tert-butyldimethylchlorosilane, stirring at 25° C. for 12 h, removing N'N-dimethylformamide in vacuo, adding water for precipitation, filtering, centrifuging and washing, and drying to obtain modified lignin.

[0036] Preparation Example 12 The preparation method of modified lignin comprises the following steps: dissolving 1.1 g of alkali lignin in 5.3 mL of N'N-dimethylformamide, adding 0.21 mg of imidazole and 0.32 mg of tert-butyldimethylchlorosilane, stirring at 20° C. for 13 h, removing N'N-dimethylformamide in vacuo, adding water for precipitation, filtering, centrifuging and washing, and drying to obtain modified lignin. Example

[0037] In the examples of the present application, polyethylene was purchased from Beijing Zhonglai Chemical Co., Ltd., vapor phase anti-rust masterbatch was purchased from Qingdao Weisinai Packaging Materials Co., Ltd., linear low-density polyethylene was purchased from Beijing Zhonglai Chemical Co., Ltd., low-density polyethylene was purchased from Beijing Zhonglai Chemical Co., Ltd., and ethylene-vinyl acetate resin was purchased from Dongguan Zhongyuan Plastic Raw Materials Co., Ltd. as EVA-150.

[0038] Example 1 A rust-proof heat shrinkable film comprises two support layers, two adhesion layers and an isolation layer, wherein the isolation layer is located between the two support layers, the adhesion layer is located between the isolation layer and the support layer, the support layer is a linear low-density polyethylene and a low-density polyethylene blended layer, the adhesion layer is an ethylene-vinyl acetate resin layer, the isolation layer is a modified polyethylene layer, and the modified polyethylene layer comprises the following raw materials in parts by mass: 50 kg polyethylene, 2.5 kg vapor phase rust-proof masterbatch, and 5 kg rust-proof aerogel, wherein the rust-proof aerogel is the rust-proof aerogel prepared in Preparation Example 1.

[0039] The preparation method of the above-mentioned anti-rust heat shrinkable film includes the following steps: polyethylene, gas phase anti-rust masterbatch and anti-rust aerogel are mixed, melt-extruded to obtain isolation layer raw materials for standby use, support layer raw materials, adhesion layer raw materials and isolation layer raw materials are fed separately, five-layer co-extruded, blow-molded to form a film to obtain the anti-rust heat shrinkable film.

[0040] Example 2 A rust-proof heat shrinkable film comprises two support layers, two adhesion layers and an isolation layer, wherein the isolation layer is located between the two support layers, the adhesion layer is located between the isolation layer and the support layer, the support layer is a linear low-density polyethylene and a low-density polyethylene blended layer, the adhesion layer is an ethylene-vinyl acetate resin layer, the isolation layer is a modified polyethylene layer, and the modified polyethylene layer comprises the following raw materials in parts by mass: 75 kg polyethylene, 3.7 kg vapor phase rust-proof masterbatch, and 8 kg rust-proof aerogel, wherein the rust-proof aerogel is the rust-proof aerogel prepared in Preparation Example 2.

[0041] The preparation method of the above-mentioned anti-rust heat shrinkable film includes the following steps: polyethylene, gas phase anti-rust masterbatch and anti-rust aerogel are mixed, melt-extruded to obtain isolation layer raw materials for standby use, support layer raw materials, adhesion layer raw materials and isolation layer raw materials are fed separately, five-layer co-extruded, blow-molded to form a film to obtain the anti-rust heat shrinkable film.

[0042] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 3.

[0043] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 4.

[0044] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 5.

[0045] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 6.

[0046] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 7.

[0047] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 8.

[0048] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 9.

[0049] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the anti-rust aerogel is the anti-rust aerogel prepared in Preparation Example 10.

[0050] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the modified polyethylene layer also includes modified lignin, and the added amount of the modified lignin is 2.65wt% of the polyethylene. The modified lignin is the modified lignin prepared in Preparation Example 11.

[0051] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the modified polyethylene layer also includes modified lignin, and the added amount of the modified lignin is 3.49wt% of the polyethylene. The modified lignin is the modified lignin prepared in Preparation Example 12.

[0052] Example 13 The difference between Example 13 and Example 11 is that in Example 13, the added amount of modified lignin is 1.25 wt % of polyethylene.

[0053] Embodiment 14 The difference between Example 14 and Example 11 is that in Example 14, the added amount of modified lignin is 5.12 wt % of polyethylene.

[0054] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, no vapor phase rust-inhibiting masterbatch is added.

[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no anti-rust aerogel is added.

[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, a polyethylene layer is used instead of a modified polyethylene layer.

[0057] Test methods The rust-proof heat shrinkable films prepared according to the raw materials and preparation methods of Examples 1-14 and Comparative Examples 1-3 were tested for tensile strength and elongation at break using an electronic universal material testing machine according to standards GB / T1040.3-2006 and GB / T6672-2001. The samples prepared according to GB / T 16267-2008 were tested for vapor phase corrosion inhibition ability. The oxygen permeability was tested according to GB / T1038-2000 "Plastic Materials and Sheets Air Permeability Test Method Pressure Difference Method". The oxygen permeability of the samples of Examples 1-14 and Comparative Examples 1-2 and the oxygen permeability change rate of Comparative Example 3 were calculated. The calculation formula is as follows, and the results are recorded in Table 1.

[0058] Change rate = (oxygen permeability of comparative example 3 - oxygen permeability of sample) / oxygen permeability of comparative example 3 × 100% Table 1 Performance test results of anti-rust heat shrink film According to Table 1, Examples 1-2 and Comparative Examples 1-3, it can be seen that the elongation breaking rate, tensile strength and corrosion inhibition ability of the rust-proof heat shrinkable film prepared in Example 1-2 are higher than those in Comparative Examples 1-3, and the oxygen permeability of Example 1-2 is lower than that of Comparative Example 3, indicating that the rust-proof heat shrinkable film prepared in Example 1-2 has good elongation breaking rate, tensile strength and rust-proof performance. The rust-proof heat shrinkable film prepared in Example 1-2 contains gas phase rust-proof masterbatch, which can slowly volatilize rust-proof particles to the outside, thereby preventing Rust particles adhere to the surface of the object in the heat shrink film to form an anti-rust layer, thereby isolating the object in the film from oxygen and water vapor to achieve rust prevention. At the same time, the volatilization rate of the gas phase anti-rust masterbatch is low, which can achieve long-term rust prevention; the addition of anti-rust aerogel can enhance the mechanical properties of the isolation layer, thereby improving the elongation fracture rate and tensile strength of the anti-rust heat shrink film. The anti-rust heat shrink film can provide protection for the object in the film for a long time. At the same time, the anti-rust aerogel contains a composite gas phase corrosion inhibitor, which can further improve the anti-rust performance of the anti-rust heat shrink film. No gas phase anti-rust masterbatch is added in Comparative Example 1, no anti-rust aerogel is added in Comparative Example 2, and a polyethylene layer is used in Comparative Example 3 instead of a modified polyethylene layer, so that the gas phase corrosion inhibition ability of Comparative Examples 1-3 decreases, the oxygen permeability increases, and the anti-rust performance decreases. The tensile strength and elongation fracture rate of Comparative Example 2 also decrease, which reduces the protective performance of the anti-rust heat shrink film.

[0059] Compared with Example 1-2, the vapor phase corrosion inhibition ability of Example 3-4 is reduced. When preparing the anti-rust aerogel used in Example 3-4, the addition amount of the composite vapor phase corrosion inhibitor was adjusted, indicating that the addition amount of the composite vapor phase corrosion inhibitor affects the performance of the anti-rust heat shrink film. When the addition amount of the composite vapor phase corrosion inhibitor is too small, it directly affects the long-term anti-rust performance of the anti-rust aerogel, thereby reducing the anti-rust performance of the anti-rust heat shrink film. When the addition amount of the composite vapor phase corrosion inhibitor is increased, the composite vapor phase corrosion inhibitor is unevenly distributed in the anti-rust aerogel and the compatibility is reduced, thereby reducing the anti-rust performance of the anti-rust aerogel.

[0060] Compared with Example 1-2, the vapor phase corrosion inhibition ability of Example 5-6 is reduced. When preparing the anti-rust aerogel used in Example 5-6, the mass ratio of sodium nitrite, sodium benzoate and dicyclohexylamine octanoate in the composite vapor phase corrosion inhibitor is adjusted, indicating that there is a synergistic effect between sodium nitrite, sodium benzoate and dicyclohexylamine octanoate. The three vapor phase corrosion inhibitors are compounded according to the mass ratio in Example 1-2, which can improve the anti-rust performance. When the mass ratio of the three changes, the anti-rust performance of the anti-rust heat shrinkable film decreases.

[0061] Compared with Example 1-2, the elongation breaking rate, tensile strength and anti-rust performance of Example 7-8 are improved. When preparing the anti-rust aerogel used in Example 7-8, the wet gel is treated with methyltrimethoxysilane. After the treatment, the shrinkage degree of the wet gel during the drying process is reduced, and the loose and porous structure of the anti-rust aerogel can be better maintained. At the same time, the wet gel is connected with hydrophobic groups, which improves the hydrophobicity of the wet gel, is beneficial to improving the porosity and structural strength of the anti-rust aerogel, and is also beneficial to the bonding of the anti-rust aerogel with polyethylene and the mechanical strength of the isolation layer.

[0062] Compared with Examples 7-8, the elongation breaking rate, tensile strength and anti-rust performance of Examples 9-10 are all reduced. When the anti-rust aerogel used in Examples 9-10 was prepared, the concentration of methyltrimethoxysilane was changed. When the concentration of methyltrimethoxysilane was reduced, the hydrophobic modification effect of the wet gel was reduced, and shrinkage occurred during the drying process, causing the pores of the rust-proof aerogel to collapse and the mechanical properties to decrease. When the concentration of methyltrimethoxysilane was increased, the hydrolysis reaction and the condensation reaction were violent, the modification process of the wet gel was uneven, the structure of the wet gel was damaged, and the mechanical properties of the rust-proof aerogel were reduced.

[0063] Compared with Example 1-2, the elongation breaking rate, tensile strength, and vapor phase corrosion inhibition ability of Example 11-12 are improved, and the oxygen permeability is reduced. Modified lignin is also added to the modified polyethylene layer of Example 11-12. The modified lignin has good antioxidant properties, which can improve the antioxidant properties of the modified polyethylene layer, and at the same time improves the ability to isolate oxygen and water vapor. While reducing the entry of water vapor and oxygen, it can improve the mechanical properties of the anti-rust heat shrinkable film, thereby improving the anti-rust performance of the anti-rust heat shrinkable film.

[0064] Compared with Examples 11-12, the elongation breaking rate, tensile strength, and vapor phase corrosion inhibition ability of Examples 13-14 are all reduced, and the oxygen permeability is increased. In Examples 13-14, the addition amount of modified lignin is adjusted. When the addition amount of modified lignin is reduced, the rust prevention performance of the rust-proof heat shrinkable film by the modified lignin is reduced, and the rust prevention performance of the rust-proof heat shrinkable film is reduced. When the addition amount of modified lignin is increased, the modified lignin is unevenly distributed in the modified polyethylene layer, which not only reduces the rust prevention performance of the rust-proof heat shrinkable film, but also reduces the mechanical properties of the rust-proof heat shrinkable film.

[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A rust-proof heat shrinkable film, characterized in that: The invention comprises two supporting layers, two adhesive layers and an isolating layer, wherein the isolating layer is located between the two supporting layers, the adhesive layer is located between the isolating layer and the supporting layer, the supporting layer is a blended layer of linear low-density polyethylene and low-density polyethylene, the adhesive layer is an ethylene-vinyl acetate resin layer, the isolating layer is a modified polyethylene layer, and the modified polyethylene layer comprises the following raw materials in parts by mass: 50-75 parts of polyethylene, 2.5-3.7 parts of gas phase antirust masterbatch, and 5-8 parts of antirust aerogel.

2. The rust-proof heat shrinkable film according to claim 1, characterized in that: The anti-rust aerogel is a silicon dioxide aerogel added with a composite gas phase corrosion inhibitor, and the addition amount of the composite gas phase corrosion inhibitor is 1.22-2.35wt% of the total weight of the anti-rust aerogel.

3. The rust-proof heat shrinkable film according to claim 2, characterized in that: The composite gas phase corrosion inhibitor comprises sodium nitrite, sodium benzoate and dicyclohexyl octanoate in a mass ratio of (0.76-0.83):(1.16-1.32):(0.54-0.63).

4. The rust-proof heat shrink according to claim 2, characterized in that: The method for preparing the rust-proof aerogel comprises the following steps: dissolving hydrochloric acid and hexadecyltrimethylammonium bromide in water, mixing them evenly, adding methyltriethoxysilane, stirring at 20-25°C for 2-2.5h, adding a composite gas phase corrosion inhibitor, stirring until the mixture is evenly mixed, adding ammonia water, standing at 75-80°C to obtain a wet gel, washing, and drying to obtain the rust-proof aerogel.

5. The rust-proof heat shrinkable film according to claim 1, characterized in that: After washing and before drying, the wet gel is further treated as follows: 18-23 wt % tert-butyl alcohol solution of methyltrimethoxysilane is added to the washed wet gel, reacted for 11-12 hours, and then freeze-dried.

6. The rust-proof heat shrinkable film according to claim 1, characterized in that: The modified polyethylene layer also includes modified lignin, and the added amount of the modified lignin is 2.65-3.49wt% of the polyethylene.

7. The rust-proof heat shrinkable film according to claim 6, characterized in that: The preparation method of the modified lignin comprises the following steps: dissolving alkali lignin in N'N-dimethylformamide, adding imidazole and tert-butyldimethylchlorosilane, stirring at 20-25°C for 12-13h, removing N'N-dimethylformamide by vacuum, adding water for precipitation, filtering, centrifugal washing, and drying to obtain the modified lignin.

8. The method for preparing the rust-proof heat shrinkable film according to claims 1-7, characterized in that: The following steps are involved: Polyethylene, gas phase antirust masterbatch and antirust aerogel are mixed and melt-extruded to obtain isolation layer raw materials for use. The support layer raw materials, adhesion layer raw materials and isolation layer raw materials are fed separately, and five layers are co-extruded and blown into thin films to obtain antirust heat shrinkable film.

Citation Information

Patent Citations

  • Synthetic fibre for reinforced concrete with rust prevention function and method for preparing same

    CN101337782A

  • Antirust film and production technique

    CN105751653A

  • Method of manufacturing aerogels using sodium silicate and aerogel tiles for making same method

    KR100705587B1

  • MIGRATING CORROSION INHIBITOR FOR STEEL REINFORCEMENT IN CONCRETE

    RU2009124188A